BALANCING ECONOMIC GROWTH AND PRESERVATION OF HUMAN RIGHTS DURING MOVEMENT CONTROL ORDER: THE MALAYSIAN EXPERIENCE IN OVERCOMING THE IMPACTS OF COVID-19 PANDEMIC (International Seminar on Syariah and Law (INSLA), 2020)
The spread of Covid-19 pandemic across the globe has triggered many countries to implement lockdown to break the chain of infection. Malaysia, like many other countries in the world, has implemented movement control order (MCO) in various stages starting on 18th March 2020 to overcome the pandemic. During this MCO period, almost every day-to-day activity has been restricted. Employees were forced to work from home, schools and universities were closed and most business activities have also been shut down. The MCO was implemented as a reflection to the government’s role to preserve public health and the right to life of its citizen. Nevertheless, the implementation of MCO has also affected the growth of Malaysian economy. This paper aims at exploring the efforts by Malaysian authorities in balancing the country’s economic growth and preserving the public health and human rights of its citizen. For this purpose, qualitative method has been used in which various primary and secondary sources have been examined. This will explore the actions taken by the government in overcoming Covid-19 pandemic as well as to overcome the economic downturn due to this pandemic. The preliminary finding from this paper indicates that, the Government of Malaysia has played its role and discharged its duty to respect, protect, and fulfil human rights of its people while addressing the Covid-19 impact. The government has used its discretion to restrict certain rights to maintain public health. At the same time, a number of stimulus packages targeted to certain affected groups have also been introduced to help reduce the burden of economic impact due to this pandemic as well as to sustain the economic growth of the country.